Resiliência e espiritualidade em pacientes oncológicos: uma abordagem junguiana - Chequini, Maria Cecilia Menegatti (2009)
This work s objective is to explore the interrelationship between resilience and spirituality in oncological patients, using as reference the Jungian theories. The term resilience was used here to describe the process through which an individual, a group or a community overcome adverse situations, transforming these in personal and collective development opportunities. Spirituality refers to the experience with the Self, which brings meaning and significance to existence. The Resilience Scale (WAGNILD e YOUNG, 1993) and the Spiritual Well-Being Scale (PALOUTZIAN e ELLISON, 1982), and a questionnaire collecting demographic religious/ spiritual and health data, were applied in a sample group of 60 people between 27 and 72 years of age (14 men and 46 women), all São Paulo City residents. At the time, all participants had been diagnosed with some type of cancer and were undergoing treatment. The statistic analysis of data showed that there is a considerably positive relationship between resilience and spiritual well-being. The applications of this study indicate that spirituality is an important factor in the process of recovery and efficient in the development of methods for the promotion of resilience